2019
DOI: 10.3390/ijms20143605
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Plays a Protective Role against Premature Ovarian Failure and Prompts Female Germline Stem Cell Survival

Abstract: This study was designed to investigate the protective effect of resveratrol (RES) on premature ovarian failure (POF) and the proliferation of female germline stem cells (FGSCs) at the tissue and cell levels. POF mice were lavaged with RES, and POF ovaries were co-cultured with RES and/or GANT61 in vitro. FGSCs were pretreated with Busulfan and RES and/or GANT61 and co-cultured with M1 macrophages, which were pretreated with RES. The weights of mice and their ovaries, as well as their follicle number, were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 51 publications
2
30
0
Order By: Relevance
“…Follicles were counted and classified as primordial follicles as shown in (E) and indicated with green arrows; primary follicles as shown in (F) and marked by cyan circles; secondary follicles as shown in (G) and indicated with blue circles; healthy antral follicles as shown in (H) and indicated with purple circles; and atretic follicles as shown in (I) and indicated with red arrows. The classification method for different stage follicles was performed mainly according to previous reports [ 56 , 57 ]. (J)–(L) Serum concentrations of IL-6, TNF-α, and LPS (n = 10–12; ∗ p < 0.05, ∗∗ p < 0.01, ∗∗∗ p < 0.001, LFD control vs LFD+DHF 10 , Student's t test; ## p < 0.01, ### p < 0.001, HFD control vs LFD control, Student's t test; &&& p < 0.001, HFD control vs HFD+DHF 5 , HF+DHF 10 , and HFD+DHF 20 , one-way ANOVA).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Follicles were counted and classified as primordial follicles as shown in (E) and indicated with green arrows; primary follicles as shown in (F) and marked by cyan circles; secondary follicles as shown in (G) and indicated with blue circles; healthy antral follicles as shown in (H) and indicated with purple circles; and atretic follicles as shown in (I) and indicated with red arrows. The classification method for different stage follicles was performed mainly according to previous reports [ 56 , 57 ]. (J)–(L) Serum concentrations of IL-6, TNF-α, and LPS (n = 10–12; ∗ p < 0.05, ∗∗ p < 0.01, ∗∗∗ p < 0.001, LFD control vs LFD+DHF 10 , Student's t test; ## p < 0.01, ### p < 0.001, HFD control vs LFD control, Student's t test; &&& p < 0.001, HFD control vs HFD+DHF 5 , HF+DHF 10 , and HFD+DHF 20 , one-way ANOVA).…”
Section: Resultsmentioning
confidence: 99%
“…Increased inflammation is closely associated with aging-related diseases, including visceral obesity, insulin resistance, and ovarian failure [ [54] , [55] , [56] , [57] ]. To examine the suppressive effect on inflammation of 7,8-DHF, we investigated representative pro-inflammatory factors, including IL-6 and TNF-α.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, studies have demonstrated that TNFα, IL-1β, and IFN-γ induce ROS production in multiple types of human cells ( Yang et al, 2007 ; Agharazii et al, 2014 ). Similarly, increased levels of pro-inflammatory factors and oxidative products have been observed in animal POI models induced by chemotherapy drugs or radiotherapy, and antioxidats can simultaneously reduce pro-inflammatory factors (TNF α, IL-6, and IL-10) and oxidative product (malondialdehyde (MDA), H 2 O 2 , and ROS) levels by activating PI3K/AKT/mTOR or inhibiting NF-κB signaling pathways, thereby improving ovarian function ( He et al, 2017 ; Liu C et al, 2018 ; Li and Liu, 2018 ; Jiang et al, 2019 ). In summary, oxidative stress can promote inflammation in the ovaries and cause ovarian aging ( Figure 3 ).…”
Section: Effects Of Oxidative Stress On Inflammation In the Ovariesmentioning
confidence: 99%
“…Antioxidants such as resveratrol and curcumin can up-regulate the expression of AKT and reduce OS level in ovarian tissue in animal models of POI, thereby regulating apoptosis in granulosa cells and improving ovarian function [ 28 , 29 ]. IL-6 is a typical immune response regulatory factor and its expression is closely related to levels of OS damage in cells or tissues, regardless of premature ovarian failure (POF) [ 30 ], polycystic ovarian syndrome (PCOS) [ 31 ], or ovarian damage caused by environmental pollutants [ 32 ]. CASP3 represents a terminal executioner caspase and can be activated by various signals including OS, which can cause DNA breakage and granulosa cell apoptosis, ultimately leading follicular atresia and damage to ovarian function [ 33 ].…”
Section: Discussionmentioning
confidence: 99%